The Persuasive Power of Religious Metaphor in Selected Qur’anic and Biblical Verses: Ontological, Structural and Orientational - Naser, Hayder Sadeq; Mohammed, Ali Badeen (Al-Adab Journal, 2020)
The issue of identifying metaphors is not clear-cut in most religious texts (Charteris-Black, 2005). For metaphors that are dealt with by religious texts such as human life as a journey or as a game, a prayer as a flowing river, the living martyrs (the living dead), a taste of death, the journey of the dead and “die, yet shall he live” are mostly spiritual matters for which academic appraisal is essential (Lakoff & Johnson, 1980; Gibbs, 2008). That is, the quality of the explanations that are presented by such metaphors need an intensive investigation, because these are the key function of metaphor in religious texts. Moreover, metaphors in sacred texts may be misjudged due to: the absence of the image in the target language and the different symbolic meanings of metaphor in the source text. Therefore, we aim to tackle such a problem via analysing the different forms and functions of metaphors in selected Qur’anic and Biblical verses. To operate such metaphorical analysis, a two-dimensional model is adapted from two different discourse analysts: aI-Sakaaki (2000) and Lakoff & Johnson (1980). The study reveals how the persuasive power of metaphor in the Qur’anic and Biblical verses related are regulated around the diversity of ontological, structural and orientational forms, and how every correlation between two domains of metaphors can shape its functions.